Electromagnetic interference shielding effectiveness of a flexible carbon fiber felt containing in situ grown hafnium carbide nanowires and nanobelts. Issue 15 (15th October 2019) - Tian, Song; Zhou, Lu; Liang, Zhongtian; Wang, Yanru; Yang, Yu; Qiang, Xinfa; Qian, Zhonghao
Abstract: Hafnium carbide nanowires (HfCnw ) and a small amount of hafnium carbide nanobelts (HfCnb ) were incorporated in a flexible carbon fiber felt by catalysis-assisted chemical vapor deposition to fabricate an electromagnetic interference (EMI) shielding carbon-based material with excellent electromagnetic wave absorption properties. The EMI shielding effectiveness (SE) of the flexible carbon fiber felt containing in situ grown HfCnw and HfCnb was investigated in X band (8.2 GHz–12.4 GHz). The result shows that more than 99% of the incident beam was shielded when the thickness of the sample is 1.5 mm. Moreover, all the SEA /SET values in this work are more than 0.8, even up to 0.94 at 11 GHz, meaning SET mainly results from SEA . The excellent electromagnetic wave absorption properties of the sample are due to the conductivity loss triggered by moving electrons and the polarization loss caused by considerable interfaces.